2023
DOI: 10.3390/molecules28104094
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany, Biological Activities and Phytochemical Compounds of Some Species of the Genus Eryngium (Apiaceae), from the Central-Western Region of Mexico

Abstract: There are approximately 250 species of Eryngium L. distributed throughout the world, with North America and South America being centers of diversity on this continent. In the central-western region of Mexico there may be around 28 species of this genus. Some Eryngium species are cultivated as leafy vegetables, ornamental, and medicinal plants. In traditional medicine they are used to treat respiratory and gastrointestinal conditions, diabetes, and dyslipidemia, among others. This review addresses the phytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 132 publications
0
6
0
1
Order By: Relevance
“…These compounds were also identified in extracts of E. maritimum , E. campestre and E. planum , and according to Cortés-Fernández et al [ 5 ] and Kikowska et al [ 8 ], they are associated with antioxidant properties that confer anti-inflammatory and antiprotozoal effects. Although these Eryngium species, including E. montanum , are used in traditional medicine for their anti-inflammatory, analgesic or antimicrobial properties, pharmacological and toxicity studies are lacking for most of them, especially regarding their root extracts [ 3 , 14 ]. However, for rosmarinic acid, identified as the main component of E. montanum extracts in this study, no toxicity in humans has been reported at doses of 100–200 mg/kg [ 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These compounds were also identified in extracts of E. maritimum , E. campestre and E. planum , and according to Cortés-Fernández et al [ 5 ] and Kikowska et al [ 8 ], they are associated with antioxidant properties that confer anti-inflammatory and antiprotozoal effects. Although these Eryngium species, including E. montanum , are used in traditional medicine for their anti-inflammatory, analgesic or antimicrobial properties, pharmacological and toxicity studies are lacking for most of them, especially regarding their root extracts [ 3 , 14 ]. However, for rosmarinic acid, identified as the main component of E. montanum extracts in this study, no toxicity in humans has been reported at doses of 100–200 mg/kg [ 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these Eryngium species, including E. montanum , are used in traditional medicine for their anti-inflammatory, analgesic or antimicrobial properties, pharmacological and toxicity studies are lacking for most of them, especially regarding their root extracts [ 3 , 14 ]. However, for rosmarinic acid, identified as the main component of E. montanum extracts in this study, no toxicity in humans has been reported at doses of 100–200 mg/kg [ 14 , 29 ]. However, it is necessary to expand studies on this topic to guarantee the efficacy and safety of consuming these extracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various species of the genus Eryngium have been reported to possess ornamental, culinary, agricultural, and medicinal applications. The aerial parts of several members of this taxon are reportedly reliable sources of diverse secondary metabolites, such as polyacetylenes, flavonoids and saponins, coumarins, and monoterpene glycosides (Cárdenas-Valdovinos et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%